Specifika personálního vedení high-tech firmy - Svoboda, Michal (Vysoké učení technické v Brně. Fakulta podnikatelská, 2011)
Diplomová práce pojednává o specifikách personálního vedení resp. řízení v podnicích s vyspělými technologiemi, označovanými high-tech. Pomocí dotazníkového šetření a strukturovaného interview je analyzována situace v personální oblasti v konkrétním high-tech podniku. Teoretická část vymezuje high-tech sektor, popisuje činnosti a účel personálního útvaru a moderní pojetí rozvoje lidských zdrojů. Dále je pojednáno o vlivu firemní kultury na strategii rozvoje lidských zdrojů, jsou zmíněny prvky leadershipu, včetně teorie generací a diversity managementu. Praktická část zahrnuje část analytickou a návrhovou, včetně zhodnocení variant.

The Master´s thesis deals with specifics of personal leadership or management in companies with advanced technologies, called high-tech. Using questionnaire investigation in addition to structured interview is analyzed situation in personal area in the high-tech company . Theoretical part defines high-tech sector, describes activities and purpose of personal unit and modern conception of development of human resources. Below is entertained about influence of corporate culture on the strategy of human ressource development. Furthermore there are mentioned elements of leadership including theory of generation and diversity management. Practical part involves analytical and recommendation part, including variants
Personal Specifics of Leading of High-tech Companies
Keywords: High-tech; firma; vedení; řízení; lidské zdroje; personální management; rozvoj; firemní kultura; tým; diverzita; High-tech; company; leadership; management; human resources; personal management; development; corporate culture; team; diversity